Qual a contribuição do surgimento da Cooperativa Piá ao município de Nova Petrópolis - Gottschalk, Felipe Antonio (Universidade do Vale do Rio dos Sinos, 2016)
In the second half of the 60 arise rumors of the emergence of a new cooperative, which sought then to unite people with the same purpose, have a place to market your products, where the result would bring benefits to the whole community. Then the Cooperativa Agropecuária Petrópolis Ltda (PIÁ). The cooperative movement is structured by seven principles, which are discussed, refined and defended in the International Cooperative Alliance (ICA) and the seventh concern with the community, local development. In this purpose the purpose of this study: what is the contribution of the emergence of PIA to municipality of Nova Petrópolis. The field research was carried out by means of a questionnaire and visits the properties selected for the job. The results show that the different programs of the cooperative bring result, making the more faithful to cooperative members, thus avoiding the great abandonment of activity on the part of the farmer.
Keywords: Cooperativa; Princípios; Preocupação com a comunidade; Cooperative; Cooperative; Principles; Concern for the communitig